2018
DOI: 10.4103/jmss.jmss_35_18
|View full text |Cite
|
Sign up to set email alerts
|

Design and construction of a laser-based respiratory gating system for implementation of deep inspiration breathe hold technique in radiotherapy clinics

Abstract: Background:Deep inspiration breath-hold (DIBH) is known as a radiotherapy method for the treatment of patients with left-sided breast cancer. In this method, patient is under exposure only while he/she is at the end of a deep inspiration cycle and holds his/her breath. In this situation, the volume of the lung tissue is enhanced and the heart tissue is pushed away from the treating breast. Therefore, heart dose of these patients, using DIBH, experiences a considerable decline compared to free breathing treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…A total of 3 studies investigated breathing motion using laser devices based on the same working principle [31,38,39]. Figure 1 provides the working principle of the instruments used in these studies.…”
Section: Recent Developmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 3 studies investigated breathing motion using laser devices based on the same working principle [31,38,39]. Figure 1 provides the working principle of the instruments used in these studies.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…The two studies showed that laser-based devices had high performance when used in clinical conditions. Farzaneh et al [31] comprehensively designed and constructed a laser-based breathing monitoring instrument, including the electronic circuits, assembly hardware (box holder and LCD holder), software for processing the signal, and phantom.…”
Section: Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients were scanned in the supine position using a breast board while their left arm was placed above the head. To perform DIBH, a novel system was used as a house respiratory gating system [22]. This system uses the CD22-100AM122 distance meter laser sensor.…”
Section: Ct Scanmentioning
confidence: 99%